Qingkailing injection ameliorates cerebral ischemia-reperfusion injury and modulates the AMPK/NLRP3 Inflammasome Signalling pathway - Chongyang Ma; Xueqian Wang; Tian Xu; Xue Yu; Shuang Zhang; Shuling Liu; Yushan Gao; Shuning Fan; Changxiang Li; Changming Zhai; Fafeng Cheng; Qingguo Wang (BMC, 2019)
Abstract Background Cerebral ischemia is the second-leading cause of death and the main cause of permanent adult disabilities worldwide. Qingkailing (QKL) injection, a patented Chinese medicine approved by the China Food and Drug Administration, has been widely used in clinical practice to treat cerebral ischemia in China. The NOD-like receptor pyrin 3 (NLRP3) inflammasome is activated in cerebral ischemia and thus, is an effective therapeutic target. AMP-activated protein kinase (AMPK) is an important regulator inhibiting NLRP3 inflammasome activation. Methods We investigated the potential of QKL injection to provide neuroprotection after cerebral ischemia in a rat model of middle cerebral artery occlusion (MCAO). Adult male Sprague-Dawley rats (210-230 g) were randomly divided into three groups which consist of sham, MCAO and 3 ml/kg QKL. Rats in the QKL group received intraperitoneal injections of 3 ml/kg QKL, while rats in other groups were given saline in the same volumes. After 90 min ischemia and 24 h reperfusion, neurological function, laser speckle imaging, brain infarction, brain water content and brain blood barrier permeability were examined and cell apoptosis at prefrontal cortex were evaluated 24 h after MCAO, and western blot and real-time quantitative polymerase chain reaction was also researched, respectively. Results Intraperitoneal administration of QKL alleviated neurological deficiencies, cerebral infarction, blood-brain barrier permeability, brain oedema and brain cell apoptosis after MCAO induction. QKL decreased pro-inflammatory cytokines, TNF-α, IL-6 and IL-1β, and increased anti-inflammatory cytokines, IL-4 and IL-10. Furthermore, QKL activated phosphorylated AMPK, decreased oxidative stress and decreased NLRP3 inflammasome activation. Conclusions QKL relieved cerebral ischemia reperfusion injury and suppressed the inflammatory response by inhibiting AMPK-mediated activation of the NLRP3 inflammasome. These results suggest that QKL might have potential in treating brain inflammatory response and attenuating the cerebral ischemia-reperfusion injury.